1997
DOI: 10.1093/clinchem/43.12.2292
|View full text |Cite
|
Sign up to set email alerts
|

Subnanogram-concentration measurement of buprenorphine in human plasma by electron-capture capillary gas chromatography: application to pharmacokinetics of sublingual buprenorphine

Abstract: We describe a sensitive and specific method for the measurement of buprenorphine in human plasma. The method involves a structural analog as an internal calibrator, careful control of pH during sample extraction to maximize drug recovery, and back-extraction into acid followed by reextraction to eliminate endogenous interferences. After evaporation, sample residues are derivatized with heptafluorobutyric anhydride and analyzed by separation on a fused-silica polymethylsiloxane capillary column and electron-cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…[19][20][21]33 AUC 0-t values found for the two 8-mg buprenorphine tablet formulations in the present study were greater than the AUC for an 8-mg tablet found by one group of investigators 20 while being within the range of the values determined by a different group of researchers. 19 There was a trend for mean Cmax values to be higher for the combination formulation than for the buprenorphine-alone tablet. This difference might be related to the failure to use identical analytic procedures or to other study differences discussed below.…”
Section: Buprenorphine Tablet Pharmacokineticscontrasting
confidence: 62%
See 1 more Smart Citation
“…[19][20][21]33 AUC 0-t values found for the two 8-mg buprenorphine tablet formulations in the present study were greater than the AUC for an 8-mg tablet found by one group of investigators 20 while being within the range of the values determined by a different group of researchers. 19 There was a trend for mean Cmax values to be higher for the combination formulation than for the buprenorphine-alone tablet. This difference might be related to the failure to use identical analytic procedures or to other study differences discussed below.…”
Section: Buprenorphine Tablet Pharmacokineticscontrasting
confidence: 62%
“…The bioavailability of an 8-mg buprenorphine tablet is approximately 35% to 50% lower than an equivalent dose of this drug in an ethanol solution. [19][20][21] Results from multiple-dose studies, however, indicate that the relative bioavailability ranges between 63% to 80% for the tablet versus solution buprenorphine formulations. [21][22][23] Buprenorphine can produce mood-elevating effects similar to those associated with the use of other µopioid receptor agonists 24 and consequently there is a potential for patients who are receiving buprenorphine tablets for maintenance therapy (ie, agonist) to selfadminister this drug by injection by dissolving the tablets.…”
mentioning
confidence: 99%
“…; Everhart et al . ), compared with 56 nM buprenorphine and 285 nM naltrexone in this study. While there are limits to the extent to which our studies in rat can be compared with clinical studies, our data suggest two things for future clinical studies.…”
Section: Discussionmentioning
confidence: 79%
“…Plasma samples were assayed by capillary gas chromatography with electron-capture detection after extraction and derivatization according to our published method. 7 The lower limit of quantitation was, depending on which run, 0.1 or 0.2 ng/mL.…”
Section: Pharmacokinetic Sampling and Assessmentsmentioning
confidence: 99%
“…3 It has recently been reported to be an effective treatment for opiate dependence. 1,[3][4][5][6][7][8][9] Buprenorphine doses in the range of 4 to 32 mg per day are required to treat opiate addiction in most patients. 1,4,5,10,11 Buprenorphine has been administered via four routes: intravenous, intramuscular, oral, and sublingual.…”
mentioning
confidence: 99%